2016
DOI: 10.1007/s10792-016-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the long-term results of trabectome surgery

Abstract: The aim of this study was to investigate the safety and efficacy of ab interno trabeculectomy which is a minimally invasive glaucoma surgery, in the late period, performed via trabectome instrument. A total of 70 eyes followed up with a diagnosis of open-angle glaucoma (OAG) and undertaken trabectome surgery were included in the study. Preoperative and postoperative intraocular pressures (IOPs), number of the drugs used, and complications were retrospectively investigated and the data were evaluated. The crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…typically stabilises in the mid-teens range. 5,26,27 These results support the consideration of the trabectome anywhere along the arc of disease where IOP in the mid-teens would be acceptable.…”
Section: Discussionmentioning
confidence: 59%
“…typically stabilises in the mid-teens range. 5,26,27 These results support the consideration of the trabectome anywhere along the arc of disease where IOP in the mid-teens would be acceptable.…”
Section: Discussionmentioning
confidence: 59%
“…We observed a significant reduction in IOP at 7 postoperative time points (Figure 2). The complete success rate of trabeculo-canalectomy at 1, 3, 6, 12 and 24 months was 92.5%, 86.8%, 94.3%, 92.5% and 90.6% respectively ( Table 2), which showed good therapeutic effects compared with previous literature [10][11][12]. International and domestic studies reported that IOP drop rate of trabeculectomy combined with anti-metabolizing drugs or releasable sutures in PACG patients was 44-70% [13].…”
Section: Discussionmentioning
confidence: 65%
“…Esfandiari et al (13) also found PEXG to be associated with a higher chance of success. Discrepancies in reports may be related to the differences in follow-up duration, considering that the reports indicating better results for PEXG had shorter follow-up periods (19)(20)(21)(22)(23). Since PEXG is associated with fibrillary protein deposition in the trabeculum, (24) it may have an initially better response to surgical operations bypassing trabecular resistance.…”
Section: Discussionmentioning
confidence: 99%